Proceeding of International Competition and Exhibition on Computing Innovation 2016 (iCE-CInno 2016) - Nor Azhar, Ahmad (Faculty of Computer Systems & Software Engineering, 2016)
The International Competition and Exhibition on Computing Innovation (iCE-CInno 2016) is an international research competition organised by Universiti Malaysia Pahang. The competition aims to promote the sprit of inventiveness among Malaysians and ASEAN participants with the theme "Communitising Innovative Computing". This competition is a platform for young inventors to introduce and exhibit their creations that optimistically will drive technologies in future.